Transformasi AI dan Kurikulum: Tantangan Pendidikan Islam menghadapi Abad ke- 21 - Irsyad, Muhammad; Zakir, Supratman (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2023)
In the 21st century, Islamic education in Indonesia faces many unprecedented dynamics.With the development of technology, globalization and the increasing demand for personal skills and needs.Challenges and obstacles in exploring the use of artificial intelligence (AI) as a tool to help transform Islamic education curricula to overcome these challengesThe role of AI in curriculum development is to be responsive and adaptive, with the ability to better personalize learning, better track learning, accurately track learning, and make informed decisions. data-based determination.AI has a positive impact in improving the quality and relevance of curricula for the implementation of AI in education. However, the integrity of AI in Islamic education with regard to ethical aspects and challenges including data privacy, digital divide, and social considerations means that the 21st century considerations are an exploration of the potential and risks of using AI in educational contexts to provide recommendations for educational stakeholders. As such, this study not only provides a philosopher's view of AI in Islamic education, but also provides a framework that can help Islamic educational institutions utilize AI to face 21st century challenges and improve the quality of education.